2013
DOI: 10.1007/s10067-013-2266-7
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus vaccine and systemic lupus erythematosus

Abstract: To investigate the association between human papillomavirus (HPV) vaccination and autoimmune manifestations compatible with systemic lupus erythematosus (SLE) or SLE-like disease, the medical history of six women who presented with SLE or SLE-like disease following HPV immunization was collected. Data regarding type of vaccine, number of immunization, family and personal, clinical and serological features, as well as response to treatments were analyzed. In the reported cases, several common features were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 44 publications
3
59
0
2
Order By: Relevance
“…The major remitting patients with immunosuppression therapy had mild adverse effects to the vaccine immediately following the first dose of the HPV vaccine and then developed heavier SLE symptoms within two months after subsequent vaccine administration. In conclusion, the authors hypothesized a potential causal link between HPV vaccination and onset or relapse of SLE [130]. Thus, although for most patients, the benefits of immunization outweigh its risks, clinicians must be aware of the odds for an autoimmune disease onset or exacerbation following HPV vaccination.…”
Section: Hpv Vaccine and Primary Ovarian Failurementioning
confidence: 93%
See 1 more Smart Citation
“…The major remitting patients with immunosuppression therapy had mild adverse effects to the vaccine immediately following the first dose of the HPV vaccine and then developed heavier SLE symptoms within two months after subsequent vaccine administration. In conclusion, the authors hypothesized a potential causal link between HPV vaccination and onset or relapse of SLE [130]. Thus, although for most patients, the benefits of immunization outweigh its risks, clinicians must be aware of the odds for an autoimmune disease onset or exacerbation following HPV vaccination.…”
Section: Hpv Vaccine and Primary Ovarian Failurementioning
confidence: 93%
“…In 2013, Gatto and coworkers investigated cases of SLE in women following HPV vaccination [130]. The onset of SLE occurred during the later doses of the HPV vaccination schedule and all the women had family histories of autoimmune disease.…”
Section: Hpv Vaccine and Primary Ovarian Failurementioning
confidence: 99%
“…By 2005 the media and Wall Street questioned the company's ability to survive, however reports of the company's' emanate death were premature [47]. [58], and the "mother" of the autoimmune diseases, SLE [57]. A recent advisory issued by the American College of Pediatricians warned of the potential of premature ovarian failure (POF) in young girls, with its significant consequences for future health and prospects of motherhood [59].…”
Section: The Arthritis Relief Miraclementioning
confidence: 99%
“…It may therefore be worth considering the use of the quadrivalent HPV vaccination, Gardasil [61]. Mok et al reported the Gardasil vaccine to be safe and reasonably effective in a group of 50 SLE patients [62].…”
Section: Human Papilloma Virusmentioning
confidence: 99%